Assessing fluoroquinolone‐associated aortic aneurysm and dissection: Data mining of the public version of the FDA adverse event reporting system. Issue 5 (25th April 2019) - Meng, Long; Huang, Jing; Jia, Yuntao; Huang, Huali; Qiu, Feng; Sun, Shusen
Summary: Aims: A recent large epidemiological study found fluoroquinolone use is associated with an increased risk of aortic aneurysm or dissection. We aimed to examine fluoroquinolone (ciprofloxacin, levofloxacin and moxifloxacin) associated aortic aneurysm or dissection through data mining of the US Food and Drug Administration Adverse Event Reporting System (FAERS). Methods: Reports to the FAERS from 1 January 2004 to 31 December 2016 were analysed. Pharmacovigilance tools were used for quantitative detection of signals that is, drug‐associated adverse events, including reporting odds ratio, proportional reporting ratio, information component given by a Bayesian confidence propagation neural network and empirical Bayes geometric mean. Sensitivity analyses that limited the data by gender and adverse event date also showed similar trends. Results: Based on 3721 adverse event reports, all three fluoroquinolones are associated with aortic aneurysm, and levofloxacin is associated with aortic dissection. The risk of aortic aneurysm is higher than the aortic dissection. Oral administration of fluoroquinolones is more likely to produce these adverse events. Conclusion: The results obtained herein are consistent with clinical observations, suggesting the necessity for further clinical research on aortic aneurysm and dissection associated with fluoroquinolones.